Design of a 57 % bandwidth microwave rectifier for powering application - Defu Wang; Renato Negra (2014 IEEE Wireless Power Transfer Conference, 2014)
This paper proposes a novel implementation of a high frequency rectifier, which is realised using the simplified real frequency technique. The optimum impedances presented at the diode package plane are found from source-pull simulation over a broad frequency range. The implemented broadband rectifiers show good performance in terms of efficiency and bandwidth. Using a HSMS 2820 Schottky diode device, greater than 50 % efficiency has been measured from 1.25 GHz to 2.25 GHz. Furthermore, greater than 60 % efficiency with 14 dB (from 12 dBm to 26 dBm) input power dynamic range is achieved at 1.8 GHz. Peak efficiency of 77 % is obtained at the input power of 23 dBm. The high efficiency over such a large bandwidth is believed to be the best reported to data in open literature at these frequencies.